Legal Apparatus, Celebrities, and Students: The Profiling of Drug Abuse Offenders in Indonesia - Henky Fernando; Yuniar Galuh Larasati; Leanne Morin (Universitas Negeri Semarang, 2025)
This study aims to explain and analyse the profiling of drug abuse offenders through cases disseminated in online news. This phenomenon tends to be overlooked in previous studies. This study is a descriptive qualitative study using a case study approach. The findings in this study show that the profiling of drug abuse perpetrators disseminated through online news is not a few who are legal apparatus (police, prosecutors, and correctional officers), celebrities (singers, actresses, and celebgrams or celebrities form instagrams), and students (elementary, junior high school, senior high school, and university). The involvement of the legal apparatus, celebrities, and students in drug abuse cases is not only as users or addicts but also as drug dealers. The findings in this study have significance for the process of uncovering the modes and motives of drug abuse so that it can be used as a basis for addressing and preventing drug abuse more constructively.